ANALISIS BEBAN KERJA DI INSTALASI LABORATORIUM - Amiroh Kurniati; Tahono Tahono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Human resources (HR) planning is associated with an institution’s strategic plan, so the study of the required number of support personnel is in line with the direction of business development planning of the Laboratory Installation Unit. WISN (work load indicator staff need) method is a calculation based on the analysis of health manpower needs of the workload (work load analysis) and is considered as the most accurate method to calculate labour requirements in short-term. Based on the results of the analysis of manpower needs at the Laboratory Installation of Lung Health of the Community Hall Surakarta, it is known that there is still a lack of a number of five (5) persons of the health laboratory staff. The persons still lacking consist of: one (1) laboratory person related to clinical pathology laboratory, one (1) laboratory person for smear microscopy laboratory, and still three (3) microbiology laboratory persons. These persons are needed to be able to carry out the activities for a good laboratory service, and quality which is in accordance with the related applicable standards.